In pursuit of economically competitive agro-tourism sector: the case of Terengganu homestay, Malaysia - Bachok, Syahriah; Tuan Mohd Amin, Tuan Anisdina; Ab Rahman, Syakir Amir (Malaysian Institute of Planners, 2018)
Agro-tourism is more than just a tourist product. It is a journey to a new sensation or positive behavior concerning the environment, the community and culture. It also one of the diversified sub-sectors that provide opportunities and choices for the rural community, commonly associated with agricultural activities to enhance and maintain their economic sustainability. This research focuses on the quantification of tourism sector income specifically related to agricultural destinations, activities, and products, evaluated in the selected communities that offer tourists visits and stays within the former’s villages or settlements. Income derived from the activities, destinations, and products are to be reported and assessed against initial investment and annual operating costs. This is an area mostly void of literature, especially those within the Malaysian contexts. The research aims at exploring the vitality and robustness of agro-tourism based homestay activities in Terengganu. Three objectives have been developed based on the gaps in existing literature. Firstly, the research is to identify offerings of homestay destinations, activities, and products relevant to agriculture sector within the rural communities of Terengganu. Secondly, the research is to assess the income received from these activities based on communal receipts as well as individually reported revenues. Finally, the research is to recommend strategic and focused areas of improvement to increase and sustain the competitiveness of agro-tourism sector delivered through homestays operation. The methods used in this paper were the semi-structured interview and focus group discussion. 76 respondents participated in the discussion.